Indicadores clave para el desarrollo y formalización de emprendimientos informales en zonas vulnerables. - Salgado-Ortiz, Patricia Janella; Preciado-Ramírez, Joffre Danny; Proaño-González, Esther Angelica (Editorial Grupo AEA, 2026)
This study analyzes the key indicators that influence the formalization of informal enterprises in vulnerable areas. The main objective is to identify the factors that allow entrepreneurs to access financing, business education, and government support. Using data from reputable institutions, the study evaluated indicators related to access to financial resources, infrastructure availability, and public support. The results show that the lack of formal credit access and business education remains a significant obstacle, but when combined with coherent public policies, formalization becomes more viable. It is concluded that formalization improves the economic and social conditions of entrepreneurs and promotes sustainable economic development invulnerable communities.